EFFECT OF A QUATERNARY AMMONIUM COMPOUNDS ON HATCHING IN BREEDER BROILER EGGS - Mustafa, Hozan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The aim of this study was to determine whether successfully different quaternary ammonium levels for sanitizing fertile eggs controlled microbial activity on eggshells and how that activity affected the hatchability of fertile eggs. Four treatments (non-sanitized the Quaternary ammonium compound at different levels 1/100, 1/200, and 1/300 ml/L of water) were randomly assigned to 660 white fertile eggs weighing an average of 67.930±0.630 gm, produced by 60-week-old Lohmann White breeder hens. before and at the tenth day of incubation. The findings demonstrated that, in comparison to quaternary ammonium at the (1/300) level, non-sanitized viable eggs had a lower hatchability and a lower percentage of dead embryos at the same level. There were no significant (P>0.05) differences recorded in egg weight among treatments at zero-day and 18th day in this study. But, at the 21st day of incubation, the egg weight was reduced in all concentrations of quaternary ammonium compared with the control group. The higher egg weight loss during the whole period of incubation (0-21 days) was recorded for quaternary ammonium (1/100) compared with both other concentrations of quaternary ammonium. Prior to being placed in the incubator, the hatching eggshell surface's total aerobic bacterial counts were considerably (P